Rheological and mechanical properties of Yttria Stabilized Zirconia (YSZ) produced by ceramic injection moulding / Mahfuzah Zainudin - Zainudin, Mahfuzah (2017)
Powder Injection Moulding (PIM) is a promising approach to producing a near netshape product of intricate geometry with cost-effective production. PIM by using ceramic powders has been studied recently due to interest as ceramic biomaterials. Yttria Stabilized Zirconia (YSZ) powders are renowned materials with their, biocompatibility, superior dimensional stability and excellent mechanical properties resulting from mechanisms of transformation toughening. The focus of this study is to fabricate root pins for dental implantation structure through Ceramic Injection Moulding (CIM). 3 mol% YSZ powders were used to mix with binder components that consist of palm stearin (PS) as a primary binder and polyethylene (PE) as a backbone binder in 60:40 ratios. Four different powder loadings were prepared in this study; 57, 58, 59 and 60 vol. % based on critical powder volume percentage (CPVP) experiment. The homogeneity of the feedstocks was evaluated via torque rheometry data and scanning electron microscopy (SEM) observation. The flow ability of the feedstock were determined through rheological characteristic which are the relationship of viscosity and shear rate formed pseudoplastic behaviour, the flow behaviour index value (n) is below than 1 and lower activation energy (E). Then, all feedstocks were injected in a screw thread shape and rectangular bar mould for further experiment. All moulded specimens were embedded into alumina powder (wicking agent) before undergoing thermal debinding process at 550°C to remove the binders and pre-sintering at 1100°C was carried out simultaneously after debinding process in the same furnace. The parts were subsequently sintered in the furnace up to 1450°C for 3 hours without wicking agent with 3°C/min heating rate. The characterization of sintered parts, physical properties, and mechanical properties was performed. It is expected that, low powder loading specimens (57 vol. %) had lower viscosity, strength, density and hardness but higher in porosity compared to higher powder loading specimens (58 vol. %, 59 vol. % and 60 vol. %). The elastic modulus of compressive strength and hardness for 60 vol. % specimens was 4.79 ± 1.24 GPa and 398.5±10.4 HV respectively. Overall, root pins for dental implantation structure was successfully fabricated via CIM technique using PS as the binder system.